Defamation through Social Media Based on Laws and Regulations - Endah Tri Wahyuni (Journal La Sociale, 2020)
In this modern era, the progress of information technology, electronic media and globalization occur almost in all areas of life. One of the crimes committed by misusing the benefit of electronic and computer technology is the defamation case through social media. Freedom of opinion in Indonesia can be seen in the Constitution of Republic Indonesia Year 1945 on Article 28 (1). This article write about What are law provisions that can be applied to the criminal act of defamation through social media, and How is the criminal responsibility of the perpetrators of defamation through social media. The method used in this research is normative legal research. The results are something could be classified as defamation in social media if proven guilty according to the 4th element in ITE LAW.